Chinese environmental contention : linking up against waste incineration - Bondes, Maria (China's environment and welfare., 2019)
"A plethora of new actors has in recent years entered China's environmental arena. In Western countries, the linkages and diffusion processes between such actors often drive environmental movements. Through a study of Chinese anti-incineration contention, this book investigates how the different contentious actors in China's green sphere link up and what this means for environmental contention. It addresses questions such as: What lies behind the notable increase of environmental protests in China? And what are the potentials for the emergence of an environmental movement?The book shows that a complex network of ties has emerged in China's environmental realm under Hu Jintao. Affected communities across the country have connected with each other and with national-level environmentalists, experts and lawyers. Such networked contention fosters both local campaigns and national-level policy advocacy. Beyond China, the detailed case studies shed light on the dynamics behind the diffusion of contention under restrictive political conditions."--